Cortical Brain Changes in Patients With Locked-In Syndrome Experiencing Hallucinations and Delusions - Sarà, Marco; Cornia, Riccardo; Conson, Massimiliano; Carolei, Antonio; Sacco, Simona; Pistoia, Francesca (Frontiers in Neurology, 2018)
Previous evidence suggests that hallucinations and delusions may be detected in patients with the most severe forms of motor disability including locked-in syndrome (LIS). However, such phenomena are rarely described in LIS and their presence may be underestimated as a result of the severe communication impairment experienced by the patients. In this study, we retrospectively reviewed the clinical history and the neuroimaging data of a cohort of patients with LIS in order to recognize the presence of hallucinations and delusions and to correlate it with the pontine damage and the presence of any cortical volumetric changes. Ten patients with LIS were included (5 men and 5 women, mean age 50.1 ± 14.6). According to the presence of indicators of symptoms, these patients were categorized as hallucinators (n = 5) or non-hallucinators (n = 5). MRI images of patients were analyzed using Freesurfer 6.0 software to evaluate volume differences between the two groups. Hallucinators showed a selective cortical volume loss involving the fusiform (p = 0.001) and the parahippocampal (p = 0.0008) gyrus and the orbital part of the inferior frontal gyrus (p = 0.001) in the right hemisphere together with the lingual (p = 0.01) and the fusiform gyrus (p = 0.01) in the left hemisphere. Moreover, a volumetric decrease of bilateral anterior portions of the precuneus was recognized in the hallucinators (right p = 0.01; left p = 0.001) as compared to non-hallucinators. We suggested that the presence of hallucinations and delusions in some LIS patients could be accounted for by the combination of a damage of the corticopontocerebellar pathways with cortical changes following the primary brainstem injury. The above areas are embedded within cortico-cortical and cortico-subcortical loops involved in self-monitoring and have been related to the presence of hallucinations in other diseases. The two main limitations of our study are the small sample of included patients and the lack of a control group of healthy individuals. Further studies would be of help to expand this field of research in order to integrate existing theories about the mechanisms underlying the generation of hallucinations and delusions in neurological patients.